Penegakan Hukum terhadap Pelanggaran Norma Adat Dayak Ngaju, atas Tindakan Kekerasan dalam Rumah Tangga (Studi di Kecamatan Tewah, Kabupaten Gunung Mas, Kalimantan Tengah) - Gery Gea Grappelly (University of Merdeka Malang, 2022)
AbstractIndonesia is a pluralistic country with a diversity of ethnic groups, who live and live throughout the Indonesian archipelago. Each ethnic group has a language, customs, religion and law enforcement against violations of customary norms that are different from one another. So far, many cases that have occurred in the community have been resolved through traditional channels such as Domestic Violence (KDRT), which always increases every year, especially in Tewah District, Gunung Mas Regency, Central Kalimantan. In addition, a legal process has also been carried out if the settlement through customary law does not find a bright spot. This study uses empirical research methods and a sociological juridical approach that provides accurate and reliable data regarding Law Enforcement Against Violations of Ngaju Dayak Customary Norms (Study in Tewah District, Gunung Mas Regency, Central Kalimantan). The basis for the authority of the relevant customary institutions is as stated in the Emergency Law Number 1 of 1951 concerning Temporary Measures to Organize the Units of PowerComposition and Procedure of Civil Courts.